MEN 2A SYNDROME – A SURPRISING CAUSE FOR SECONDARY HYPERTENSION. (June 2018) - Mihalcea, R.; Homentcovschi, C.; Naidin, O.; Nicolita, C.; Siliste, R.; Ciomag, R.
Abstract : Objective: A 52 years old female, diagnosed for 4 years with hypertension, presents in the Emergency Departament with headache and BP = 180/110 mmHg. Her past medical history included a LBBB diagnosed for 3 years (the patient denied any chest pain and/or proofs of myocardial ischaemia). Prior to this current presentation she received treatment with Perindopril 5 mg/dy, Trimetazidine 70 mg/dy, Acetylsalycilic acid 75 mg/dy. Design and method: On admission no signs of heart failure, heart rate 80 bpm, BP = 180/110 mmHg (right and left arm). The patient received treatment with i.v. Furosemide and i.v. Enalapril and as chronic treatment, Amlodipine 5 mg. The ECG showed NSR with 76 bpm and features consistent with LBBB. Her echocardiogram showed changes consistent with hypertensive cardiomyopathy and paradoxical movement of the interventricular septum (given the presence of LBBB) with an EF of 55% and normal kinetics. Abdominal ultrasound showed normal kidneys and normal velocities in the renal arteries. Thyroid ultrasound showed multiple nodular lesions, findings that indicated polinodular goiter. Lab tests were unremarkable, with the exception of a slightly increased calcium level, elevated PTH values, in a patient who was never investigated for a secondary etiology for hypertension. Calcitonin levels were normal. Results: We suspected a secondary endocrine etiology for HBP and proceeded to measurements of renin, aldosterone and fractionated plasmatic metanephrine; pheocromocytoma was confirmed by higher levels of metanephrins and nor-metanephrins and also by the presence of a mass in the left adrenal gland at CT- scan. Serum calcium was high with a high PTH and borderline normal vitamin D levels prompted us to take into consideration the diagnosis of primary hyperparathyroidism. Given the presence of primary hyperparathyroidism and pheocromocytoma, even without medullary thyroid carcinoma, we diagnosed a MEN-2a syndrome. The patient received a dose of 2 mg daily of Doxazosin and reffered for surgical resection of the adrenal mass, with a good postoperative evolution and no antihypertensive drugs needed. Conclusions: This case is special because of the lack of suggestive symptoms for pheocromocytoma, that postponed the diagnosis; the entire picture is of a complex disease, that has to be properly managed.